Depression Among Elderly Patients /Mosul City - Alyasiri, Abdul Rasoul (AL-Kindy College Medical Journal, 2017)
Background: Depression in elderly aged (60 year and above )is a widespread mental health problem . The current primary healthcare systeminadequately recognize and treat elderly patients with depression.. Objectives:To determine the prevalence of depression among elderly patientsin Mosul city, its correlation with some sociodemographic variablesand to assess severity of depression in relation to past history of depression. Type of the study: This is a cross-sectional study. Methods: This study assess the prevalence of depression in a randomly selected sample 150 elderly patients aged 60 years and above (89 female & 61 male) who attended the geriatric clinic in Ibn Sina Teaching Hospital /Mosul City between the 1st/March /2014 to the 10th /June 2014.A short form of Geriatric Depression Scale (GDS) the Arabic version was used to assess depressionand a semi-structured interview were applied after screening the patients for cognitive impairment using the Mini Mental State Examination (MMSE) to exclude those who scored less than 23 on this scale . Results:The study showed that the Prevalence of depression was 65.3% , statistically significant difference was not found with any variable used. Strong positive relation was found in severely depressed patients with the past history of depression, multiple physical complaint was found in the depressed sample. Conclousin:As the prevalence of depression among elderly patients was high , National programs should be developed in community & health services focusing on early detection and treatment of depression among the elderly population.